Construction of Graphene‐Based "In‐Paper" 3D Interdigital Microelectrodes for High Performance Metal‐Free Flexible Supercapacitors. Issue 5 (6th March 2022) - Jiang, Xuening; Gao, Rixia; Liu, Gang; Luo, Hao; Zhao, Xueping; Jiang, Lei
Abstract: Flexible micro‐supercapacitors (MSCs) are promising power sources of portable/wearable electronic devices. Electrodes are the key components determining performance of the MSCs, but it still remains a big challenge in either materials or fabrication methods to achieve both high charge storage capability and robust mechanical flexibility. Herein, a novel water‐cooling assisted selective laser ablation (WASLA) technique is demonstrated for scale‐fabrication of "embedded‐in‐paper" 3D graphene‐cellulose composite interdigital electrodes (3D GCCIEs) in a mask‐free and chemical‐free manner. The obtained electrodes are endowed with 3D charge storage geometry, high electrical conduction, freely designed patterns, and the inherent advantages of paper substrate. Therefore, the 3D GCCIEs‐based MSC exhibits excellent overall performance including large specific capacitances, high rate performance, impressive cyclic stability, and remarkable mechanical flexibility. Moreover, metal‐free 3D GCCIE‐MSC integrated arrays with diverse shapes composed of linear/curved interdigital electrodes are also fabricated, and a letter‐shaped MSC array successfully lit a light emitting diode light in both flat and folded status demonstrating excellent device flexibility. The as‐fabricated 3D GCCIE‐MSCs have shown great application potential as power sources of flexible electronic devices, and the WASLA method proves to be an effective strategy for scale‐manufacturing high performance paper‐based charge storage devices not limited to supercapacitors. Abstract : Graphene‐based "in‐paper" interdigital microelectrodes constructed by a novel and facile water‐cooling assisted selective laser ablation technique are endowed with 3D charge storage geometry, high electrical conductivity, freely designed patterns, and the advantage of the paper substrate, based on which metal‐free supercapacitors with large capacitances, robust mechanical flexibility, excellent cyclic stability, shape diversity, and facile integration are achieved.